Development and preliminary clinical feasibility of a Delphi-based aerobic exercise prescription for children with asthma - Zhang, Ying; Kong, Ze; Yang, Kaixuan; Li, Zhiqiong; Yu, Ziye; Liu, Longyan; Meng, Chenxiao; Zhang, Jie (Frontiers in Pediatrics, 2025)
ObjectiveThis study aims to develop a clinically applicable aerobic exercise prescription for children with asthma using a two-round Delphi consensus process and to preliminarily evaluate its feasibility and safety of this prescription in a pre–post pilot study. The secondary goal was to explore preliminary signals of changes in exercise capacity, pulmonary function, and asthma control among asthmatic children after implementing the prescription—with consideration of potential confounding factors such as concurrent medication use and inhaler technique retraining—thereby providing preliminary evidence for non-pharmacological interventions in pediatric asthma management.MethodsSemi-structured interviews were conducted with 10 parents of asthmatic children, 10 medical professionals, and 10 sports rehabilitation experts to develop an initial aerobic exercise prescription based on the FITT (frequency, intensity, time, type) principle. Subsequently, this initial prescription was iteratively refined through two rounds of Delphi consultation involving 17 experts (specializing in pediatric pulmonology, pediatric nursing, and exercise rehabilitation). A consensus threshold of ≥75% agreement and authority metrics were predefined, and item-level expert feedback was used to modify the prescription. Finally, a 12-week prospective outpatient pilot study was conducted, including 15 asthmatic children aged 6–14 years who implemented the finalized prescription. Feasibility (recruitment rate, exercise adherence), safety (asthma-related adverse events), and clinical outcomes [6 min walk distance (6MWD), spirometry, Childhood Asthma Control Test (C-ACT)] were measured.ResultsFor the Delphi process, all 17 experts completed both rounds of consultation, with an effective response rate of 94.44% in Round 1 and 100% in Round 2. The expert authority coefficient (Cr) was 0.86, and the coefficient of variation (CV) for item importance scores decreased across rounds (from 0.07–0.16 in Round 1 to 0.07–0.13 in Round 2), indicating high expert consensus. For the pilot study, the recruitment rate reached 100%, and the average weekly exercise adherence was 2.7 ± 0.3 sessions. The incidence of asthma-related adverse events was 13.3% (mild wheezing and coughing), which did not interrupt training. Post-intervention outcomes showed significant improvements: 6MWD increased from 510.07 ± 31.96 to 539.27 ± 44.52 m (P < 0.001); forced expiratory volume in 1 s (FEV1)% predicted increased from 76.87 ± 5.63 to 87.61 ± 7.24 (P < 0.001); and C-ACT score increased from 17.60 ± 1.76 to 22.13 ± 1.46 (P < 0.001).ConclusionsThe aerobic exercise prescription developed via the Delphi method is feasible and safe for short-term application in children with asthma, with preliminary signals of potential improvements in exercise capacity, pulmonary function, and asthma control. Notably, these observations may be influenced by confounding factors, including concurrent asthma medication adherence and standardized inhaler technique retraining. Due to the small sample size and uncontrolled pre–post design of the pilot study, definitive conclusions on efficacy or independent intervention effects cannot be drawn.